2012
DOI: 10.5194/bg-9-2419-2012
|View full text |Cite
|
Sign up to set email alerts
|

Production of oceanic nitrous oxide by ammonia-oxidizing archaea

Abstract: Abstract. The recent finding that microbial ammonia oxidation in the ocean is performed by archaea to a greater extent than by bacteria has drastically changed the view on oceanic nitrification. The numerical dominance of archaeal ammonia-oxidizers (AOA) over their bacterial counterparts (AOB) in large parts of the ocean leads to the hypothesis that AOA rather than AOB could be the key organisms for the oceanic production of the strong greenhouse gas nitrous oxide (N2O) that occurs as a by-product of n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
226
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(244 citation statements)
references
References 52 publications
16
226
1
1
Order By: Relevance
“…Thus, 15 N accumulating in the N 2 O pool contributed a very minor fraction of 15 N accumulating in the NH 2 OH pool. Previous studies demonstrate that N 2 O production during NH 3 oxidation in enrichment culture from oceanic water samples, enrichments, and N. maritimus only contribute up to two parts per thousand of NO 2 − produced (29). A similar rate of N 2 O production by N. maritimus cells during our experiments would yield an estimated 70 nM N 2 O over the course of our entire experiments.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Thus, 15 N accumulating in the N 2 O pool contributed a very minor fraction of 15 N accumulating in the NH 2 OH pool. Previous studies demonstrate that N 2 O production during NH 3 oxidation in enrichment culture from oceanic water samples, enrichments, and N. maritimus only contribute up to two parts per thousand of NO 2 − produced (29). A similar rate of N 2 O production by N. maritimus cells during our experiments would yield an estimated 70 nM N 2 O over the course of our entire experiments.…”
Section: Discussionmentioning
confidence: 50%
“…One possible caveat to this interpretation is that accumulation of 15 NH 2 OH was measured by IR-MS after its conversion to 15 N 2 O. Recent reports demonstrated that archaeal NH 3 oxidation produces N 2 O (28) albeit no biochemical pathway for its production in AOA has been identified (29). Production of N 2 O either by N. maritimus itself or chemical reactions affording N 2 O in our growth media, e.g., through decomposition of NH 2 OH, could potentially yield N 2 O that would interfere with NH 2 OH isotopic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that PTIO is only effective during active growth of N. viennensis (which was observed; Figure 1), or perhaps PTIO was ineffective at chelating rapidly cycling NO at the high cell densities used in the MR chamber. N 2 O in N. viennensis cultures originates from the abiotic reaction of biotic N-oxide intermediates with medium or cellular components Previous studies measuring N 2 O in pure and enrichments cultures of ammonia-oxidizing Thaumarchaea suggested an enzymatic origin of measured N 2 O (Santoro et al, 2011;Loscher et al, 2012;Jung et al, 2014); however, control experiments to test for abiotic reduction of NO to N 2 O, including by medium components, were not performed. We observed a high rate of NO reduction to N 2 O in FWM both in the presence of an NO-donating molecule and in the presence of NH 2 OH plus heat-killed cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that NO was either released as a free intermediate during ammonia oxidation by N. maritimus, or it could serve a functional role as an electron delivery mechanism to ammonia monooxygenase, an idea that has been proposed previously . Although the detection of nitrous oxide (N 2 O) has been reported for both enrichments and pure cultures of Thaumarchaea engaged in ammonia oxidation (Santoro et al, 2011;Loscher et al, 2012;Jung et al, 2014;Stieglmeier et al, 2014b), the isotope data reported by Stieglmeier et al (2014b) revealed that ammonia-oxidizing Thaumarchaea cannot enzymatically reduce NO 2 − to N 2 O via NO in the pathway known as 'nitrifier denitrification'. Several publications have suggested that ammoniaoxidizing Thaumarchaea are a major source of N 2 O to the environment based on their relative abundance in oxic environments, the isotopic signature of the detected N 2 O, and that the authors failed to detect known bacterial denitrification genes and pertinent activities (Santoro et al, 2011;Loscher et al, 2012;Jung et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrification-related processes (the oxidation of NH 2 OH and NO 2 − reduction) mediated by AOB are recognised to be a main pathway of N 2 O emission from arable soils (G dde and Conrad 1999;Zhu et al 2013;Huang et al 2014a). The traditional viewpoint that soil ammonia oxidation and associated N 2 O emission is exclusively carried out by AOB has been challenged by the discovery of amoA and nirK genes in AOA strains (Venter et al 2004;Lund et al 2012) and by the demonstration of the N 2 O production capacity of AOA enriched or isolated from arable soils and marine ecosystem (Jung et al 2011(Jung et al , 2014Santoro et al 2011;Loscher et al 2012). In most soils, AOA outnumbers AOB abundance, a common feature in multiple ecosystems (Leininger et al 2006;He et al 2007;Hu et al 2013), and a high AOA ammonia oxidation activity has been assessed in certain soils (Yao et al 2011;Zhang et al 2012;Hu et al 2015).…”
Section: Introductionmentioning
confidence: 99%